Improving Publlic Speaking Ability through Speech - Dina Amelia; Afrianto Afrianto; Samanik Samanik; Suprayogi Suprayogi; Budi Eko Pranoto; Ingatan Gulo (Journal of Social Sciences and Technology for Community Service (JSSTCS), 2022)
Public Speaking is one of the most important skills one should have. In the industrial 4.0 era, the ability to speak and elaborate on certain issues and topics in front of the public is highly significant due to the fact that now information can no longer be limited. Information is available on the internet, especially on social media. Therefore, in order to avoid misunderstanding the content of the information, public speaking ability is needed. The ability helps people to grasp information correctly. Moreover, the public speaking ability also teaches how to convince people which will be useful for those who are working and also for job seekers. This article discusses the public speaking skills of SMA Way Jepara students, especially in grades 11 and 12. The students are encouraged to practice their speaking ability. They are given some materials and topics that would help them to be more confident. After the 2nd meeting was conducted most of the students were able to gain a much better speaking ability and they also became more confident.